Reproductive Coercion: Prevalence and Risk Factors Related to Relationship Health Knowledge and Skills - Taylor, Sarah (Journal of interpersonal violence, 2025)
Reproductive coercion is any behavior that limits a person’s reproductive decision-making and can lead to negative health and safety outcomes. Previous research has explored reproductive coercion prevalence rates in clinical samples, as well as demographic risk factors for experiencing reproductive coercion. The purpose of this study is to assess the prevalence rates of two specific forms of reproductive coercion, pregnancy coercion and condom manipulation, in an ethnically and racially diverse sample of young females. We also explore the association between relationship health knowledge and skills with reproductive coercion. We used a sample of 143 females with previous sexual activity. Participants were diverse in terms of race, ethnicity, sexual orientation, and family immigration status. Descriptive statistics and logistic regression analyses were used to determine prevalence rates of pregnancy coercion and condom manipulation and the likelihood of experiencing reproductive coercion based on participants’ knowledge and skills related to relationship health. Results revealed that 16.1% of the sample had experienced reproductive coercion, with all participants in this group reporting lifetime experiences of pregnancy coercion. Lifetime experiences of condom manipulation were reported by 6.3% of the sample. The most common form of reproductive coercion experienced by participants was being told by a partner not to use any birth control. Furthermore, results indicate that higher relationship health knowledge may be a protective factor for pregnancy coercion and condom manipulation. Likewise, higher decision-making skills in relationships and higher confidence in relationships may also protect against condom manipulation. Results from this study suggest implications for sexual and relationship health programming that expands education around consent, choice, decision-making, and communication around the use of contraception.